REKONSTRUKSI KARAKTER FIKSI KE DUNIA NYATA ANALISIS FENOMENA COSPLAYER DI INDONESIA - Friscilla Naldia Bevani; Elsypa Lora Travianti; Fariz Diansyah Rizki (Journalism, Public Relation and Media Communication Studies Journal (JPRMEDCOM), 2022)
This study uses phenomena to explore self-identity and self-image from the cosplay community in Indonesia. They form self-identity and self-image not only from environmental influences but even from technological influences. Actually, self-identity and self-image can be formed by learning from childhood to adulthood. The process of forming self-identity and self-image can be through internalization and the experiences they get. Showing off unique costumes is a form of channeling their hobby and pleasure to cosplayers. The teenage years have become one of the most fans in the world of cosplay. Cosplay is a place for them to express themselves and find identity through the characters they play in this world of cosplay. The knowledge gained in this research is how the process of communication and messages conveyed by cosplayers when communicating about their identity. takes place in the formation of a cosplayer's self-identity. So that research with the phenomenological method is the right choice. The focus of his research is on existing and developing phenomena. However, literature studies were selected in this study for data collection. The Google Scholar database which is the source of data based on this research. The results based on this study have the same hobbies and the same background as the main factors in the formation of cosplay souls and cosplay communities. They have a positive self-concept, they are involved starting from their hobby of watching anime, online games and even liking Japanese culture. Cosplay costumes are a form of self-identity and self-concept, which of course are influenced by the same background and the same environment.